Successful Treatment of Scleredema Diabeticorum by Combining Local PUVA and Colchicine: A Case Report - Chayada Kokpol; Natta Rajatanavin; Ploysyne Rattanakemakorn (Karger Publishers, 2012)
Scleredema is a rare condition of unknown pathogenesis. It is classically divided into three types, based on its association with postinfection (usually streptococcal), monoclonal gammopathy and diabetes mellitus (scleredema diabeticorum). Scleredema diabeticorum often has a subtle onset, persistent involvement and is refractory to therapies. Numerous therapies have been tried, with mixed and inconsistent results. We report herein a case of scleredema diabeticorum that was successfully treated by combining local PUVA with colchicine.